Analyzing the roughness of the discontinuous surface in Mt. Semeru Eruption rock - Pradani, Diana Irmawati; Sutoyo, Heru Dwiriawan; Suhardono, Agus (Journal of Earth and Marine Technology (JEMT), 2023)
From the moment they were formed to the deposition process, the characteristics and properties of rocks that form on the earth's surface vary. The effects of Mount Semeru's eruption will be transported and deposited, eventually solidifying into rock masses. As a result of weak places like joints, fractures, and fissures, where the density, filling, and orientation are not continuous, rock masses in nature have discontinuous or discontinuous qualities. Rock shear strength will be decreased if there are discontinuous planes in the rock bulk. Using Barton's empirical equation and the Joint Roughness Coefficient (JRC) parameter, roughness conditions in discontinuous planes can be measured. Determining the features of the rock mass that are influenced by the shear strength of discontinuous planes in the Mount Semeru eruption rock based on variations in shear roughness in accordance with Barton and Choubey's criterion is therefore crucial. The observation of discontinuous plane roughness conditions in rocks as a result of Mount Semeru's eruption is necessary to get many rock shear strength parameters, which are then used to determine the friction angles, undulation values, and cohesion values in the surface of the discontinuous plane.